Analyse interprétative du discours du Landscape Urbanism et impact sur le développement des pratiques des paysagistes dans le contexte français - Anaïs Leger-Smith (Projets de Paysage)
This paper examines the influence that Landscape Urbanism has on the development of Landscape Architects’ professional practices in the French context. Ten years ago, in the United States, Charles Waldheim developed the theory of Landscape Urbanism, which positions the landscape architect as being the most capable profession of organizing the city by integrating ecological sciences at the very centre of urban design. This paper proposes an interpretative discourse analysis on Landscape Urbanism in parallel with similar theories and discourses in the French sphere. We suggest that Landscape Urbanism is a professional discourse that legitimates the expertise of Landscape Architects, and proposes a classification of emergent landscape design practices. We then show that Landscape Urbanism strengthens the discipline of Landscape Architecture in education and academic research. Will Landscape Urbanism, in the long term, acquire the status of critical theory, capable of provoking a mutation of the profession towards more innovative practices?